2021
DOI: 10.1038/s41598-021-86596-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autogenous crack self-healing on mechanical strength recovery of cement mortar under various environmental exposure

Abstract: While research on self-healing of cement-based materials has recently gained considerable attention and made sizable progress, there is still ongoing debate and controversy regarding the effect of crack closing induced by autogenous self-healing on mechanical strength recovery. Despite that several techniques have been used to capture and quantify the self-healing of surface cracks, the resulting effect on mechanical strength has not, to date, been explored and quantified in a rigorous and systematic manner. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
1
6
0
1
Order By: Relevance
“…However, measurements were found to be independent from calcite precipitation and mainly influenced by the formation of CSH phases 35,36,39,114 . Results of Suleiman et al 123 agree with these findings and show that the regain of strength is most pronounced for samples incorporating fly ash due to the ongoing pozzolanic reaction. A similar behavior of latent hydraulic cements is expected by the latter authors.…”
Section: Assessment Of the Efficiency Of Autogenous Self‐healingmentioning
confidence: 55%
“…However, measurements were found to be independent from calcite precipitation and mainly influenced by the formation of CSH phases 35,36,39,114 . Results of Suleiman et al 123 agree with these findings and show that the regain of strength is most pronounced for samples incorporating fly ash due to the ongoing pozzolanic reaction. A similar behavior of latent hydraulic cements is expected by the latter authors.…”
Section: Assessment Of the Efficiency Of Autogenous Self‐healingmentioning
confidence: 55%
“…The efficacy of self-healing in cementitious materials is significantly affected by the composition of cement matrix, encompassing factors such as the type and proportion of cement, the moisture level, aggregate characteristics, and the duration of the healing period [31][32][33][34][35]. Huang et al [32] reported that slag cement pastes exhibit a higher potential for autogenous healing compared to Portland cement pastes.…”
Section: Autogenous Healingmentioning
confidence: 99%
“…Conforme explicado por ROIG FLORES et al [12] e REDDY e RAVITHEJA [44], um aditivo cristalino apresenta características hidrofílicas, promovendo o aumento da densidade do C-S-H e a redução da permeabilidade do concreto. Além disso, os produtos de hidratação gerados pela mistura cristalina promovem a densificação da microestrutura e reduzem a sucção capilar [50]. Logo, os arranjos internos dos poros dos concretos são influenciados pelas fissuras, afetando a absorção capilar de água [51].…”
Section: Absorção De áGua Por Capilaridadeunclassified